Improving Performance Of CIGS Thin Film Solar Cells Numerical Modelling Through The Interface Behaviours - Nur Jasmine Binti Jalalludin (2023)
A simulation study of a Cu(In,Ga)Se2 (CIGS) thin film solar cell using ZnS as a buffer layer has been carried out in this project. Since the used of CdS in the development process is a toxic material and non-environmental friendly, new buffer layer materials that are Cd-free like Zn(S,O), ZnMgO, ZnS and In2S3 have become main research in the development of the CIGS solar cell in these recent years. In designing an efficient CIGS thin film solar cell, it is important to understand the structural and electronic properties of each element layer in the heterojunction cell. Important parameters such as thickness of layer, doping concentration, electron affinity and bandgap energy are identified before being simulate using Silvaco TCAD ATLAS Software. In the first case study, the performance of ZnS as a buffer layer is compared with CdS to ensure it is suitable for replacement and it is shown that ZnS achieved a higher efficiency of 19.89%. Second case study is varying the thickness of ZnS buffer layer in order to identify its optimum thickness. Based on the results and specification, 0.1μm is chose as the optimum thickness. Then, the bandgap energy of the CIGS absorber layer is varied and 1.21eV is selected as the optimum value. Last case study is to validate the ZnS buffer layer as a substitution by comparing its performance with other materials like CdS, ZnSe, InS and ZnO. The performance and optimum value of the case studies are based on the Voc, Isc, fill factor and efficiency obtained from the simulation.